2022
DOI: 10.1051/0004-6361/202143000
|View full text |Cite
|
Sign up to set email alerts
|

A decade-long magnetic monitoring of Vega

Abstract: Aims. The very weak magnetic field detected at the surface of Vega hints at a widespread population of weakly magnetic stars of A and B spectral types. We contribute here to gather more clues about the origin of this magnetism by investigating the long-term stability of the field geometry of this prototypical star. Methods. We use spectropolarimetric data collected as part of a long-term campaign, with more than 2,000 observations spread between 2008 and 2018. Using various sub-sets extracted from the whole ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…The LSD profiles are shown in Figure 6. Running ZDI (Semel 1989) on polarization signatures close to the detection threshold is not ideal, but previous studies have shown that it is possible to reconstruct magnetic maps even when the signatures are dominated by noise, provided that a sufficient number of observations are combined together in the inversion process (Petit et al 2010(Petit et al , 2022. Here we use the ZDI implementation of Folsom et al (2018aFolsom et al ( , 2018b in a procedure closely following the one presented by Petit et al (2021).…”
Section: Zeeman Doppler Imagingmentioning
confidence: 99%
“…The LSD profiles are shown in Figure 6. Running ZDI (Semel 1989) on polarization signatures close to the detection threshold is not ideal, but previous studies have shown that it is possible to reconstruct magnetic maps even when the signatures are dominated by noise, provided that a sufficient number of observations are combined together in the inversion process (Petit et al 2010(Petit et al , 2022. Here we use the ZDI implementation of Folsom et al (2018aFolsom et al ( , 2018b in a procedure closely following the one presented by Petit et al (2021).…”
Section: Zeeman Doppler Imagingmentioning
confidence: 99%
“…The strongest magnetic field reported (≈20 kG inferred dipolar strength) for a seemingly chemically normal O-type star is of NGC 1624-2 [61,67]. The detection of "ultra-weak" magnetic fields in Vega [68,69], an intermediate-mass A-type star, has been surprising. A few other A-type stars have been discovered to host ultra-weak fields, although they possess chemical peculiarities typically associated with the Am class [70,71].…”
Section: From Ap/bp To Oba Starsmentioning
confidence: 99%